Sefarad but not Spain : the settlement of Jews in Gibraltar, 1704-1783 - Madway, Lorraine (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 1993)
Jews arrived in Gibraltar shortly after a combined force of English andDutch soldiers occupied the Rock in 1704, during the War of SpanishSuccession. Most of them were descendants of «gerushim» who left Spainin 1492 and went to northern Morocco. The struggle of Jews to settle andestablish a community in Gibraltar parallels and, indeed, is a result of thestruggle of the British to control the fortress whose strategic position theyhad long appreciated. Initially, Jewish merchants and interpreters madethemselves useful by providing commercial and diplomatic services to thegarrison that no one else could provide. Just as the British occupationwithstood the test of repeated Spanish assaults during the course of theeighteenth century, so too, did Jews manage to rebuff the periodic attemptsof British governments to remove them. Through service and persistence,Jews finally won the right to settle in the town and establish acommunity. The presence of a flourishing Sephardic community withinplain view of Spain's shores is surely one of the ironies of Spanish-Jewishhistory which makes its study a subject of continuing fascination.